CONCEPTUALIZATION OF EXISTENTIAL THEOLOGY IN A HISTORIOGRAPHICAL PERSPECTIVE - Shevchenko, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
The article examines the correlation between Christian theology and existentialism. While religious and atheistic existentialism has been studied since its emergence, the methodological and ideological correlation of existentialism with Christian theology, especially concerning post-existentialist thinking, remains underexplored. One of the most relevant topics is the emergence and conceptualization of existential theology. The aim and tasks. The aim of this investigation is to analyze the specifics of the correlation and mutual influence of Christian theology and existentialism. The tasks are to scrupulously cover a wide range of both foreign and Ukrainian sources devoted to the study of the works of representatives of existential theology, primarily Paul Tillich and John Macquarrie. Research methods. The research methodology consists of systemic, historical, dialectical and analytical approaches, which allowed us to objectively analyze and interpret the multifaceted processes of integration of existentialism with theology. Due to the use of comparative, hermeneutic and contextualization methods, we managed to compare, contrast and synthesize diverse ideas, views and assessments of researchers of the heritage of outstanding theologians, who are little known in Ukraine. Discussion. Numerous foreign studies confirm a rather obvious arbitrariness in the definition and classification of the main postulates of religious philosophers and theologians, both existentialists and existential thinkers, which indicates the presence of methodological contradictions in the assessment of the phenomenon of classical existentialism in general and existential theology in particular. Conclusions. The analysis of the influence of Paul Tillich’s ideas on theology reveals notable developments in foreign research in recent years. At the same time, Ukrainian humanities still exhibit a significant gap in the study of the legacy of classical philosophical and theological existentialism. John Macquarrie aims to modernize theological language and revive faith by interpreting God as the ground of possibility for all existence, or as «the power that makes being possible.» The Scottish thinker, on the one hand, draws on existentialist methodology in addressing theological issues, while on the other, he does not reject the constructive role of reason in defining the principles underlying the functioning of contemporary Christian theology. The synthesis of these two approaches reflects his effort to rationalize and refine existential theology and existentialist thought more broadly, in response to the need for their continued development and conceptual clarification.